Congestion Cost Analysis and Potential Loss of Private Vehicle on Jalan Jenderal Sudirman, Jakarta - Adita Utami; Cut Lutfiah Zulfa; Asep Yayat Nurhidayat; Teuku M. Rasyif; Nurul Fajar Januriyadi (Majalah Ilmiah Pengkajian Industri, 2022)
In recent years, many big cities have experienced congestion in the world, including DKI Jakarta. Rapid economic growth has led to high demand for travel in the City, and rapid urbanization is one of the causes of traffic congestion. Traffic congestion is a characteristic of urban areas caused by increased economic activity, increased productivity of population movement, and inadequate facilities. Traffic congestion causes lost travel time, losses due to vehicle emissions, and increases traffic accidents. This study discusses the amount of costs incurred by vehicle users who pass Jenderal Sudirman street when experiencing congestion. This study aims to provide an overview for private vehicle users of the amount of costs incurred when using a private vehicle when passing Jenderal Sudirman street. The method used in determining Vehicle Operational Costs (VOC) is a method developed by the Institute for Affiliation and Research and Industry (LAPI) ITB 1997, while getting lost costs due to congestion is reviewed based on VOC and time value with the Income Approach method. The results show a high difference in operational costs and the loss of time value which is the total cost loss due to congestion on the road. Keywords:  Congestion, Vehicle operating Cost, Lost Costs, Income approach